Konseling Kelompok Berbasis Solution-Focused Brief Counseling (SFBC) untuk Kemandirian Peserta Didik - Romiaty, Romiaty; Sendayu, Fendahapsari Singgih; Feronika, Nopi; Nonsihai, Nonsihai; Amanda, Febriani; Jelita, Bernadet (Universitas Palangka Raya, 2026)
Student empowerment is a crucial component of personal, social, and academic development. Within the context of guidance and counseling, the Solution-Focused Brief Counseling (SFBC) approach offers a practical framework for strengthening students’ capacities to make autonomous decisions, solve problems, and engage in positive self-direction. This article presents a literature-based study employing a narrative review approach to examine the effectiveness of SFBC-based group counseling services in empowering students. Relevant literature published between 2021 and 2024 was retrieved from national and international databases. The findings indicate that SFBC effectively enhances student empowerment through strength-oriented strategies, measurable goal setting, and the construction of positive change narratives. When implemented in a group counseling format, SFBC further amplifies these outcomes through supportive peer interactions and collaborative social dynamics. This article provides recommendations for optimizing the application of SFBC within school counseling services and identifies potential directions for future research.